2001
DOI: 10.1002/1097-4644(20010601)81:3<507::aid-jcb1064>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐propionic acid, a melatonin‐related molecule, protects hepatic microsomal membranes from iron‐induced oxidative damage: Relevance to cancer reduction

Abstract: Excessive free iron and the associated oxidative damage are commonly related to carcinogenesis. Among the antioxidants known to protect against iron-induced oxidative abuse and carcinogenesis, melatonin and other indole compounds recently have received considerable attention. Indole-3-propionic acid (IPA), a deamination product of tryptophan, with a structure similar to that of melatonin, is present in biological fluids and is an effective free radical scavenger. The aim of the study was to examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…The cell membrane is a selective barrier that protects the cell interior and its structure and functions are susceptible to alterations as a consequence of interaction with metals. Although the interaction of iron ions with cell membranes has been insufficiently studied (Ohba et al, 1994;Karbownik et al, 2001;Brunet et al, 1999), it has been reported that high concentrations of iron ions change neuronal membrane fluidity (Ohba et al, 1994).…”
Section: Abbreviationssupporting
confidence: 84%
“…The cell membrane is a selective barrier that protects the cell interior and its structure and functions are susceptible to alterations as a consequence of interaction with metals. Although the interaction of iron ions with cell membranes has been insufficiently studied (Ohba et al, 1994;Karbownik et al, 2001;Brunet et al, 1999), it has been reported that high concentrations of iron ions change neuronal membrane fluidity (Ohba et al, 1994).…”
Section: Abbreviationssupporting
confidence: 84%
“…6 D ), confirming previously published results reported by us (17). IPA is a deamination product of dietary tryptophan, and it is a powerful antioxidant (40). Production of IPA is completely dependent on the presence of the gut microflora in particular Clostridium sporogenes (17).…”
Section: Resultsmentioning
confidence: 99%
“…6 E ). IPA protects primary neurons and hepatocytes from oxidative stress‐induced cell death (40, 41). As we observed increased hepatic oxidative stress in GF compared with conventional mice following TAA treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin is the major indoleamine synthesized from tryptophan in organisms and is an important molecule that provides cellular protection and antioxidant activity. Several structurally related indoles, including 5‐hydroxytryptophan , 5‐methoxytryptophol , N‐acetylserotonin and indole‐3‐propionic acid , as well as pinoline, a ß‐carboline formed by condensation between indoleamines and aldehydes, may also act as powerful radical scavengers while stabilizing membranes .…”
Section: Melatonin Protects Against Membrane Rigidity Due To Lipid Pementioning
confidence: 99%